Bladder injury and success rates following retropubic mid-urethral sling: TVT EXACT™ vs. TVT™. (March 2016) - Thubert, Thibault; Canel, Virginie; Vinchant, Marie; Wigniolle, Ingrid; Fernandez, Hervé; Deffieux, Xavier
Abstract: Objective: Although placement of a retropubic mid-urethral slings (MUS) is one of the gold standard surgical treatments for stress urinary incontinence, new devices are poorly evaluated before marketing. We compared TVT-EXACT™ (TVT-E), a new device expected to reduce bladder injuries, with the historically described bottom-to-top TVT™ (TVT). Study design: This retrospective study compared TVT-E ( n  = 49) and TVT ( n  = 49). The main outcomes were the prevalence of complications (bladder injuries, immediate postoperative pain, perioperative complications, etc.) and the short-term success rate (no reported urinary leakage and negative cough test) of both MUSs. Results: Minimum follow-up was 12 months. The characteristics of the two groups were comparable. The prevalence of bladder injury for TVT-E and TVT was 8% and 6%, respectively ( p  = 1). The intensity of immediate postoperative pain (VAS/100) was lower following TVT-E than after TVT (8.0 vs. 15.9, p  = 0.01). The first post-void residual was increased in the TVT-E group (153.9 vs. 78.9 mL, p  = 0.045), and there were more postoperative bladder outlet obstruction (BOO) symptoms in the TVT-E group (24% vs. 6%, p  = 0.02). However, there was no difference when considering only de novo BOO (14% vs. 4%, p  = 0.16). The prevalence of peri- and post-operative complications was equal in the two groups. The success rate was similar at 12 months of follow-up (80 vs. 82%, p  = 1). Conclusion: The prevalence of bladder injury was unchanged with TVT-EXACT™ compared with TVT™, but post-operative pain was decreased. The success rate of both retropubic MUSs was similar at 12 months of follow-up.